Natural resources, child mortality and governance quality in African countries - Sosson Tadadjeu; Henri Njangang Ndieupa; Simplice Asongu; Brice Kamguia (African Governance and Development Institute (AGDI), 2021)
This paper contributes to the literature by investigating the effect of natural resources on under-five mortality in a sample of 50 African countries over the period 1996 to 2018. We also examine the extent to which governance shapes the relationship between natural resources and under-five mortality. Our results show that natural resources have increased under-five mortality. Resource rents also have detrimental effects on child mortality by age, gender, and the three major causes of infant mortality from infectious diseases. However, an extended analysis of different types of natural resources suggests that point resources (such as oil, natural gas and mineral rents) increase under-five mortality, in contrast to the diffuse resources (such as forest rent). We also find that governance mitigates the positive effect of natural resources on child mortality. Corresponding governance policy thresholds that should be attained in order to reverse the positive effects of natural resources on child mortality are provided. We thus suggest an increase in the funds allocated to the health sector from resource rents and encourage efforts to improve governance standards in sampled countries.
Keywords: J13; O55; Q33; Q34; Q38; 330; Natural resources; Child mortality; Governance; Africa